Բանահյուսական հեքիաթի մշակման և փոխադրության արդի միտումները - Վարդանյան, Նվարդ; Վարդանյան, Նարինե (Զանգակ հրատ.)
За последние десятилетия сборники народных сказок, составленные на основе литературной обработки, хотя и мало, но издавались. В них содержатся близкие к оригиналу ценные обработки, как обогащенные своеобразным авторским подходом (А. Кочарян, Л. Хечоян), так и созданные по совершенно новым необычным принципам (Г. Бабаян). А некоторые писатели представляют известные сказочные сюжеты, переосмысливая их или наделяя современными комментариями (А. Восканян, А. Оганян, Н. Адалян). Помимо художественных обработок в настоящее время на литературном рынке большое место занимают сборники, составленные фольклористами, в которых народный материал подвергнут языковому переложению, а непонятные и замысловатые диалектные формы представлены в смягченном виде (А. Назинян, Н. Акопян, А. Газиян, С. Варданян). Такие популярные сборники весьма способствуют распространению народного материала на новом уровне. Though nowadays the folklore tale is not told to that extent it used to, it continues its development in literature. Author approaches to folklore material is currently quite different starting from literary adaptation to language expositions. Only a few collections of folklore tales created through literary adaptations have been recorded in recent decades. They contain both high–quality adaptations close to material with unique author approaches (S. Qocharyan, L. Khechoyan) and completely new adaptations created with extraordinary principles (G. Babayan). Some authors give new meaning or contemporary interpretations to the plots of famous folklore tales (A. Voskanyan, A. Ohanyan, N. Adalyan). Besides literary adaptations, the collections drawn up by folklorists take up a large place in the contemporary literary market, where folklore material is subjected to language expositions, while non–understandable and abstruse dialectal forms are mitigated (A. Nazinyan, N. Hakobyan, A. Ghaziyan, S. Vardanyan). Such popular collections are very favorable to put folklore material into circulation once again.
Keywords: Բանասիրություն